2003
DOI: 10.1007/s00402-002-0459-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the transverse metatarsal arch of the foot with gait analysis

Abstract: According to our results, TMA of the foot does not exist as described by Kapandji.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 3 publications
0
36
0
3
Order By: Relevance
“…Unbalanced distribution of load may be a reason of stress fractures and may lead to high pressure on metatarsal heads. 36 The results of this study showed that the absolute impulse of M2 was significantly higher at preferred foot. The second metatarsal is the most frequently fractured bone and carries the greatest loads during gait, compared to the other metatarsals.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Unbalanced distribution of load may be a reason of stress fractures and may lead to high pressure on metatarsal heads. 36 The results of this study showed that the absolute impulse of M2 was significantly higher at preferred foot. The second metatarsal is the most frequently fractured bone and carries the greatest loads during gait, compared to the other metatarsals.…”
Section: Discussionmentioning
confidence: 55%
“…In generally, only one foot analyzed for plantar pressure investigation according to the previous data supposed that there were no significant differences between the right and left foot in pedobarographic assessment and gait biomechanics. 35,36 While dynamic pedobarography provides insight into the plantar pressure parameters during dynamic activities such as walking and running, static pedobarography gives plantar pressure data in standing position. 19 In this study, there were no significant differences between preferred and nonpreferred foot regarding the relative pressure-loads (%) in static condition.…”
Section: Discussionmentioning
confidence: 99%
“…Lu ger et al and Ka nat lı et al fo und that the re was no dis tal trans ver se me tatar sal arch du ring the stan ce pha se. 15,18 In our study we ha ve se en a hig her per cen ta ge (80.5%) of pa ti ents had lo we ring of TMA whe re as 19.5% of pa ti ents had TMA du ring we ight be a ring. It is unders to od that lo we ring of TMA is a pat ho lo gi cal si tu a ti on sin ce the lat ter gro up (19.5%) is in the nor mal pres su re dis tri bu ti on ran ge.…”
mentioning
confidence: 59%
“…16 So me aut hors sug gest that TMA existed, whi le ot hers sug gest that the re is no func ti o nal me ta tar sal arch of the fo ot. 17,18 The Ame ri can As so ci a ti on of Ort ho pa e dic Sur ge ons sum med up the cur rent be li ef in the USA as; "A trans ver se arch is sug ges ted to exist at the MTH when no we ight is be ing bor ne; it do es not exist du ring we ight-be a rin g". Lu ger et al and Ka nat lı et al fo und that the re was no dis tal trans ver se me tatar sal arch du ring the stan ce pha se.…”
mentioning
confidence: 99%
“…Previous techniques that have been developed for measuring the transverse arch of the forefoot include plantar pressure measurements [1][2][3] , ultrasonography 4,5) , and X-ray photography 6) . In plantar pressure measurements, dropping of the transverse arch of the foot is indicated by the concentration of plantar pressure on the 2 nd or 3 rd metatarsal heads.…”
Section: Introductionmentioning
confidence: 99%